Experiences of cancer survivors in Europe: Has anything changed? Can artificial intelligence offer a solution? - Hesso, Iman; Kayyali, Reem; Charalambous, Andreas; Lavdaniti, Maria; Stalika, Evangelia; Lelegianni, Maria; Nabhani-Gebara, Shereen (Frontiers in Oncology, 2022)
Introduction: Cancer is a major global health issue. Despite technological advancements in oncology, challenges remain in many aspects related to cancer management. This study constitutes one part of the user requirement definition of INCISIVE EU H2020 project, which has been designed to explore the full potential of artificial intelligence based technologies in cancer imaging. The study aimed to explore cancer survivors’ experiences of cancer care in five European countries. Methods: A qualitative study employing semi-structured interviews was conducted. A purposive sampling strategy was used to recruit participants across the five validation countries of INCISIVE project: Greece, Cyprus, Spain, Italy, and Serbia. Forty cancer survivors were interviewed between November 2020 and March 2021. Data was analysed thematically using the framework approach and coded using NVivo12 software. Results: The analysis yielded several gaps within the cancer care pathway which reflected on the participants experiences. Five key themes were revealed; (1) perceived challenges during the cancer journey, (2) the importance of accurate and prompt diagnosis, (3) perceived need for improving cancer diagnosis, (4) absence of well-established/designated support services within the pathway and (5) suggestions to improve cancer care pathway. Conclusion: Cancer survivors experienced significant burdens pertaining to cancer diagnosis and treatment. Our findings underscored some main gaps within the cancer care pathway which contributed to the challenges articulated by the participants including lack of resources and delays in diagnostic and treatment intervals. Additionally, several suggestions were provided by the cancer survivors which could be considered towards the improvement of the current state of care, some of which can be optimised using new technologies involving AI such as the one proposed by INCISIVE.